IMPLEMENTASI METODE TILAWATI DALAM MENINGKATKAN HASIL BELAJAR BACA AL-QUR’AN SANTRI RA. AL-MUJTAMA’ PLAKPAK PEGANTENAN PAMEKASAN - Abdul Waris Albar (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2022)
The background of the research is the problems that occur in education, the lack of enthusiasm for student learning. The method of learning to read the Qur'an at home is different from at school. The lack of knowledge of parents in guiding children to learn to read the Qur'an. The formulation of the problem of this thesis that the First: How are the results of learning to read the Qur'an of RA students. Al-Mujtama’ Plakpak Pegantenan Pamekasan. Second: how is the implementation of the Tilawati method in improving the results of learning to read the Qur’an of RA students. Al-Mujtama’ Plakpak Pegantenan Pamekasan. Third, what are the supporting and inhibiting factors for the implementation of the Tilawati method in improving the learning outcomes of reading the Qur'an of RA students. Al-Mujtama’ Plakpak Pegantenan Pamekasan. This type of research was a field research that collected the primary data through interviews from the head of the madrasa, madrasa teachers and Al-Mujtama Foundation’s Al-Qur'an builder. The secondary data from literature and documents were then analysed qualitatively, in descriptive form. The results of the research that the results of students’ learning to read the Qur'an were quite good by using the tilawati method. The function of the tilawati method as a way or path taken by the teacher to teach reading the Qur'an with classical techniques and read deeply. As a result, they can read the Qur’an properly and correctly according to the rules of recitation. The factors supported the quality of teachers, student intelligence, facilities. Inhibiting factors of students’ social conditions that are the differences in methods at home and school. Latar belakang penelitian ini adalah permasalahan yang terjadi dalam dunia pendidikan, yaitu kurangnya semangat belajar siswa. Metode pembelajaran membaca Al-Qur'an di rumah berbeda dengan di sekolah. Kurangnya pengetahuan orang tua dalam membimbing anak belajar membaca Al-Qur'an. Rumusan masalah tesis ini yaitu Pertama: Bagaimana hasil belajar membaca Al-Qur'an santri RA. Al-Mujtama’ Plakpak Pegantenan Pamekasan. Kedua: Bagaimana penerapan metode Tilawati dalam meningkatkan hasil belajar membaca Al-Qur’an siswa RA. Al-Mujtama’ Plakpak Pegantenan Pamekasan. Ketiga, Apa saja faktor pendukung dan penghambat penerapan metode Tilawati dalam meningkatkan hasil belajar membaca Alquran siswa RA. Al-Mujtama’ Plakpak Pegantenan Pamekasan. Jenis penelitian ini adalah penelitian lapangan yang mengumpulkan data primer melalui wawancara dengan kepala madrasah, guru madrasah dan pembina Al-Qur'an Yayasan Al-Mujtama. Data sekunder dari literatur dan dokumen dianalisis secara kualitatif, dalam bentuk deskriptif. Hasil penelitian bahwa hasil belajar membaca Al-Qur'an siswa cukup baik dengan menggunakan metode tilawati. Fungsi metode tilawati sebagai cara atau jalan yang ditempuh guru untuk mengajar membaca Al-Qur'an dengan teknik klasikal dan baca simak. Alhasil, mereka bisa membaca Al-Qur’an dengan baik dan benar sesuai kaidah tajwid. Faktor tersebut didukung kualitas guru, kecerdasan siswa, fasilitas. Faktor penghambat kondisi sosial siswa yaitu perbedaan metode di rumah dan di sekolah